The Influence Of Love On Landon Carter's Behavior InNicholas Sparks' A Walk To Remember (1999): A Behaviorist Perspective - Juwati, Juwati, Drs. Abdillah Nugroho, M. Hum, Titis Setyabudi, S.S. M. Hum (2014)
This research paper is analyzed by using behaviorist approach elaborates the influence of love on the major character's behavior in A Walk to Remember novel. The objective of the research is to analyze the novel based on behaviorist approach. This research paper belongs to a descriptive qualitative research. The data of the research is the novel entitled A Walk to Remember. The data source comes from primary data and secondary data. The primary data source is A Walk to Remember novel and secondary data source of the research are biography of the author, websites, and other source about behaviorist criticism that support the analysis. The method to analyze this data is descriptive analysis. Based on the behaviorist criticism analysis, the researcher concludes that several relationships have a great contribution in shaping one's personality and behavior. From behaviorist analysis the influence of love on the major character can be seen from the family relationship, friend relationship, and romance relationship that appear in the novel. Every relationship gives different influence. Those influences make him improve his life better by learning from his experiences during his life.